Formal education, malaria preventive behaviour, and children's malarial status in Tanzania - Ninja Klejnstrup Ritter; Joel Silas Lincoln (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
In this study, we assess formal education as a causal determinant of women's malaria preventive behaviour, as well as children's risk of malaria infection. For identification, we rely on exogenous variation in educational attainment generated by educational reforms during the 1970s. We use data from a total of four rounds of either Demographic and Health Surveys or Malaria Indicator Surveys, which allows us to explore variation in relationships over time. In the earliest survey rounds (2004-05 and 2007-08), our results indicate that each additional year of schooling increased women's probability of using malaria prophylaxis during pregnancy by between 3.7 and 14.5 percentage points, and their children's probability of sleeping under an insecticide-treated bed net (ITN) by between 1.8 and 3.0 percentage points. Results for both women's use of ITN and children's malaria status are inconclusive across all survey rounds. We argue that differences in magnitude and strength of evidence of causality between effect estimates for women's use of malaria prophylaxis and women's and children's use of ITN is likely due to differences in the mechanisms linking these outcomes to education, with the latter being mediated by income to a higher degree than the former.
Keywords: I12; I20; O15; 330; health behaviour; malaria; school reform; Tanzania